Pengukuran Kinerja Rumah Sakit Umum Daerah Raden Mattaher Provinsi Jambi Dengan Konsep Balanced Scorecard - Rahmadani, Ima; Wijaya, Rico; Lutfi, Lutfi (Magister Ilmu Akuntansi Universitas Jambi, 2025)
This study aims to answer the question of how the financial performance of Raden Mattaher Regional General Hospital, Jambi Province, can be evaluated in terms of efficiency and effectiveness of budget management using the Balanced Scorecard (BSC) concept. The research employs a descriptive qualitatitative approach with a case study method, in which the data analyzed consist of official hospital financial reports for 2023 and 2024 obtained through an online desk study. The analysis was carried out by calculating several financial ratios, including profit margin, current ratio, collection period, return on investment, debt to asset ratio, asset turnover, and cost recovery rate. The findings indicate that the hospital’s financial performance in 2024 experienced a significant decline compared to previous year. In addition, liquidity and solvency ratios showed a worsening trend, while the effectiveness of asset utilization also decreased. The study provides practical implications in the form of recommendations for revenue diversification, improving operational cost efficiency, and strengthening performance-based financial governance. Theoretically, the results enrich the body of knowledge regarding the implementation of the Balanced Scorecard in measuring the performance of regional public hospitals as public service agencies with BLUD status.